Bilingualism in Qur'an Learning at TPQ Darussalam Benjor Village, Tumpang District: Sociolinguistic Approach - Riznima Azizah Noer; Moch Rizki Fadlillah; Lola Laula Lutfia Rahma (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
This study aims to analyze the phenomenon of bilingualism in Qur'an learning at TPQ Darussalam, Benjor Village, Tumpang District, Malang Regency. This activity is part of a community service program employing the Asset-Based Community Development (ABCD) method. This approach focuses on developing the local potential and strengths of the community. Data were collected through observation and documentation of dialogues between student teachers and learners during the learning process. Based on the collected data, five dialogue excerpts were identified, illustrating interactions that occurred during teaching activities. From these data, three main forms of bilingual communication were found, namely language shift, code-switching, and code-mixing. The findings suggest that the use of bilingualism plays a crucial role in fostering effective communication and strengthening social bonds between teachers and students within the context of community-based religious education.